Perencanaan Pembangkit Listrik Tenaga Surya Off-Grid Pada Gedung Serbaguna Pondok Pesantren Sejahtera - Ridwan, Wahyu; Tharo, Zuraidah; Rahmaniar (Universitas Medan Area, 2024)
Energy plays an important role in everyday life, for example solar energy which is one of the renewable energies which is an alternative energy for producing electricity. The electrical energy produced comes from solar radiation through the conversion of photovoltaic cells. The higher the solar radiation that hits the photovoltaic cells, the higher the electrical power produced. The Sejahtera Islamic Boarding School Multipurpose Building is a building that is used as a place for various activities, both Koran recitation activities for students, character building seminars for students or creative activities that can develop students' individual skills. With so many activities, the use of electrical energy is large every day. Therefore, in this research, an Off-Grid Solar Power Plant Plan will be made at the Sejahtera Islamic Boarding School Multipurpose Building to meet the electrical energy needs of the Multipurpose Building. Planning for the Solar Power Plant at the Sejahtera Islamic Boarding School uses an Off-Grid PLTS system with 30 solar panels with a capacity of 500 Wp, LiFePO4 type batteries with specifications of 12V 200Ah, 1 inverter with a power of 12,000 W and an SCC with a capacity of 500 A. In the planning of the PLTS generating power of 10,550 Wp per day.